Related complications of angioplasty and stenting in the treatment for intracranial atherosclerotic stenosis - Xin LI; Ning MA; Lian LIU; Zhong-rong MIAO (Chinese Journal of Contemporary Neurology and Neurosurgery, 2013)
Intracranial atherosclerotic stenosis causes acute ischemic stroke in a significant number of patients. Nowadays, the percutaneous transluminal angioplasty and stenting (PTAS) is a major method for the treatment of intracranial atherosclerotic stenosis, which can be used in patients with acute or subacute ischemic stroke, especially in patients with severe intracranial arterial stenosis, avoiding the onset of stroke. The periprocedural and long-term complications include implantation failure, intracranial bleeding, vessel rupture, embolism and in-stent restenosis. Medical treatment with anticoagulant drugs in periprocedural stage may prevent for the happening of complications.